0827 Obstructive Sleep Apnea in a Congenital Central Hypoventilation Syndrome Patient Post-Tracheostomy Ventilated with Diaphragmatic Pacing. (25th May 2022) - Cocozza, Victoria; Kim, David; Hansen, Shana; Frey, William
Abstract: Introduction: Congenital central hypoventilation syndrome (CCHS) is a rare, autosomal dominant disorder associated with a genetic mutation in the PHOX2B gene. While the treatment of CCHS requires lifelong ventilatory support, advancements in management have allowed for life expectancies comparable to healthy individuals. Prolonged lifespan of CCHS patients presents new challenges with regards to the chronic management of the disease, including the concurrence of obstructive sleep apnea (OSA) in patients ventilated with diaphragmatic pacing post decannulation. Report of Cases: A 23-year-old female with a past medical history of adenotonsillectomy and CCHS with nocturnal ventilatory support via diaphragmatic pacer (DP) was referred to sleep clinic by her pulmonologist for an evaluation of increased obstructive events and worsening nocturnal hypoxia. The patient did not require daytime ventilatory support and did not complain of any sleep-related symptoms. The DP was implanted at age 17 and the patient previously had a tracheostomy from age 3 months until decannulation at 18 years. She had a surgical closure a year later. The DP settings were titrated by her pulmonologist and monitored with repeat home sleep apnea testing (HSAT) to achieve optimal control of central hypoventilation. After an initial period of response, however, subsequent HSATs showed a progressive increase in obstructive breathing events associated with hypoxia. Further adjustments in the DP settings did not successfully correct the findings. An in laboratory polysomnography (PSG) confirmed moderate OSA with significant hypercapnia. At clinic follow-up, the patient was offered positive airway pressure therapy but chose to defer decision-making until pulmonary follow-up. The patient was also referred to ENT for an anatomic evaluation to look for potential causes contributing to upper airway obstruction. Conclusion: DP remains a treatment option for select patients with CCHS. Limited studies have shown that OSA can occur in patients with CCHS using DP as their primary management modality. Our case demonstrates the importance of keeping a broad differential in evaluating the development of concurrent OSA in these patients. Potential contributors to developing OSA include weight gain, tracheomalacia or tracheal stenosis resulting from longstanding tracheostomy status, and effects of increased DP amplitude settings. Support (If Any):